PENERAPAN METODE DECISION TREE ALGORITMA C4.5 UNTUK KLASIFIKASI MAHASISWA BERPRESTASI - Nadiya Hijriana; Riadhul Muttaqin (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
Informatic Engineering is a field of study from Information Technology Faculty (FTI) at Islamic University of Kalimantan (UNISKA). Informatic Engineering was established in 2007 and it has around 2441 students until now included by student who has graduated and student who still studying. Fact of so many students in Informatic Engineering can make a lot of data that it can used as strategic resource for Faculty to manage and monitoring of academic activity. This research using Decision Tree Method from Algorithm C4.5 and RapidMiner 5.3 as software for making classification of achievement students in field of study Informatic Engineering at Islamic University of Kalimantan. The result can be used as tool for monitoring of academic activity and it can help Faculty to improve the quality of their students. Keywords: Classification, Data, Student, Algoritma C4.5